Targeting Well-Being and Physical Activity through Sport Education in Higher Education. Issue 4 (2nd October 2022) - Li, Longxi; Moosbrugger, Michelle E.; Mullin, Elizabeth M.; Wang, Anni; Louis, Michael
ABSTRACT: During the pandemic, sedentary behavior and social isolation threatened college students' physical and mental health. The effectiveness of Sport Education on combinations of variables associated with well-being and physical activity was explored. Undergraduate students ( N  = 236) participated in a 15-week intervention; Sport Education (experimental) was compared to Direct Instruction (control). A structural equation modeling approach and Causal Mediation Analyses were conducted to test hypothesized models. A mixed factorial ANOVA was used to examine physical activity engagement. Sport Education students participated in physical activity significantly longer than the Direct Instruction group at posttest; student perceived role and task orientation significantly predicted physical activity engagement, social dysfunction, and perceived stress in the Sport Education condition. Given the climate, college students became more task-oriented, socially supported, and stress relieved through Sport Education. Future longitudinal and qualitative inquiries are encouraged to examine the effectiveness of Sport Education in motivating lifelong physical activity and well-being.